In Search of a Better Country: Migration and Prosperity Hermeneutics in Contemporary African Pentecostalism - Asamoah-Gyadu, J. Kwabena (PentecoStudies, 2018)
This article reflects on migration in the prosperity hermeneutics of contemporary Pentecostals. Prosperity, involving human flourishing in both its spiritual and physical senses is a predominant theme in Pentecostal preaching. In most of Africa this theme resonates with the life ambitions of the upwardly mobile youth in particular. This is because it addresses major concerns regarding the tragedies of poverty and failure in leadership with its attendant social problems on the continent. A lot of the people who risk their lives on the Mediterranean Seas in search of a "better country" do so on Christian prophetic inspiration. The association of living in the West in particular with prosperity and flourishing has found its way into contemporary Pentecostalism's discourses of prosperity as one of the several ways in which God blesses his children. Abraham is usually the iconic biblical example in the prosperity hermeneutics of migration. Thus, international migration may ultimately have economic implications, but for a lot of African Pentecostals, living in the developed West in particular could be a sign of God's favour, blessing and divine breakthrough. In this study, I consider prosperity preaching in these movements in order to help readers appreciate the relationship between migration and prosperity as an important dimension of contemporary bPentecostal religion.